Extracellular vesicles from Echinococcus granulosus larval stage: Isolation, characterization and uptake by dendritic cells. - María Celeste Nicolao; Christian Rodriguez Rodrigues; Andrea C Cumino (PLoS Neglected Tropical Diseases, 2019)
The secretion of extracellular vesicles (EVs) in helminth parasites is a constitutive mechanism that promotes survival by improving their colonization and adaptation in the host tissue. In the present study, we analyzed the production of EVs from supernatants of cultures of Echinococcus granulosus protoscoleces and metacestodes and their interaction with dendritic cells, which have the ability to efficiently uptake and process microbial antigens, activating T lymphocytes. To experimentally increase the release of EVs, we used loperamide, a calcium channel blocker that increases the cytosolic calcium level in protoscoleces and EV secretion. An exosome-like enriched EV fraction isolated from the parasite culture medium was characterized by dynamic light scattering, transmission electron microscopy, proteomic analysis and immunoblot. This allowed identifying many proteins including: small EV markers such as TSG101, SDCBP, ALIX, tetraspanins and 14-3-3 proteins; proteins involved in vesicle-related transport; orthologs of mammalian proteins involved in the immune response, such as basigin, Bp29 and maspardin; and parasite antigens such as antigen 5, P29 and endophilin-1, which are of special interest due to their role in the parasite-host relationship. Finally, studies on the EVs-host cell interaction demonstrated that E. granulosus exosome-like vesicles were internalized by murine dendritic cells, inducing their maturation with increase of CD86 and with a slight down-regulation in the expression of MHCII molecules. These data suggest that E. granulosus EVs could interfere with the antigen presentation pathway of murine dendritic cells inducing immunoregulation in the host. Further studies are needed to better understand the role of these vesicles in parasite survival and as diagnostic markers and new vaccines.